Increase in nonnative understorey vegetation cover after nonnative conifer removal and passive restoration. (24th August 2019) - Sample, Martha; Aslan, Clare E.; Policelli, Nahuel; Sanford, Robert L.; Nielsen, Erik; Nuñez, Martín A.
Abstract: Nonnative conifers are widespread in the southern hemisphere, where their use as plantation species has led to adverse ecosystem impacts sometimes intensified by invasion. Mechanical removal is a common strategy used to reduce or eliminate the negative impacts of nonnative conifers, and encourage native regeneration. However, a variety of factors may preclude active ecological restoration following removal. As a result, passive restoration – unassisted natural vegetation regeneration – is common following conifer removal. We asked, 'what is the response of understorey cover to removal of nonnative conifer stands followed by passive restoration?' We sampled understorey cover in three site types: two‐ to ten‐year‐old clearcuts, native forest and current plantations. We then grouped understorey species by origin (native/nonnative) and growth form, and compared proportion and per cent cover of these groups as well as of bare ground and litter between the three site types. For clearcuts, we also analysed the effect of time since clearcut on the studied variables. We found that clearcuts had a significantly higher average proportion of nonnative understorey vegetation cover than native forest sites, where nonnative vegetation was nearly absent. The understorey of clearcut sites also averaged more overall vegetation cover and more nonnative vegetation cover (in particular nonnative shrubs and herbaceous species) than either plantation or native forest sites. Notably, 99% of nonnative shrub cover in clearcuts was the invasive nonnative species Scotch broom ( Cytisus scoparius ). After ten years of passive recovery since clearcutting, the proportion of understorey vegetation cover that is native has not increased and remains far below the proportion observed in native forest sites. Reduced natural regeneration capacity of the native ecosystem, presence of invasive species in the surrounding landscape and land‐use legacies from plantation forestry may inhibit native vegetation recovery and benefit opportunistic invasives, limiting the effectiveness of passive restoration in this context. Abstract in Spanish is available with online material. Resumen: Las coníferas exóticas están ampliamente distribuidas en el hemisferio sur, donde su uso como especies forestales ha dado lugar a impactos adversos en los ecosistemas, algunas veces potenciados por su invasión. La eliminación mecánica es una estrategia comúnmente utilizada para reducir o eliminar los impactos negativos de las coníferas exóticas y promover la regeneración de especies nativas. Sin embargo, diversos factores pueden impedir la restauración ecológica activa luego de la eliminación. Como resultado, la restauración pasiva, es decir la regeneración de la vegetación natural sin intervención humana, es común después de la eliminación de coníferas exóticas. En este trabajo nos preguntamos: ¿cuál es la respuesta de la cobertura de sotobosque a la eliminación de los rodales de coníferas exóticas seguida de restauración pasiva? Muestreamos la cobertura de sotobosque en tres tipos de sitios: talas rasas de dos a diez años de edad, bosque nativo y plantaciones actuales. Agrupamos las especies del sotobosque por origen (nativas / exóticas) y forma de crecimiento, y comparamos la proporción y el porcentaje de cobertura de estos grupos, así como de suelo desnudo y hojarasca, entre los tres tipos de sitios. En el caso de las talas rasas, también analizamos el efecto del tiempo desde la tala en las variables estudiadas. Encontramos que las talas rasas tenían una proporción significativamente más alta de cobertura vegetal exótica que los sitios de bosque nativo, donde la vegetación exótica estaba casi ausente. El sotobosque de los sitios talados también presentó una mayor cobertura de vegetación total y de vegetación exótica (en particular, arbustos exóticos y especies herbáceas exóticas) en comparación con los sitios de plantación y bosque nativo. Notablemente, el 99% de la cobertura de arbustos exóticos en las talas rasas estuvo dado por la especie exótica invasora retama ( Cytisus scoparius ). Luego de diez años de recuperación pasiva desde la tala, la proporción de cobertura de vegetación nativa en el sotobosque no ha aumentado y se mantiene muy por debajo de la proporción observada en los sitios de bosque nativo. La reducida capacidad de regeneración natural del ecosistema nativo, la presencia de especies invasoras en el paisaje circundante, y los legados del uso de la tierra debido a las plantaciones, podrían inhibir la recuperación de la vegetación nativa y beneficiar a los invasores oportunistas, limitando la efectividad de la restauración pasiva en este contexto.